PENGEMBANGAN PERANGKAT PEMBELAJARAN FISIKA MENGGUNAKAN MODEL GUIDED INQUIRYYANG DILENGKAPI PENILAIAN PORTOFOLIO PADA MATERI GERAK MELINGKAR - Chodijah, Siti; Fauzi, Ahmad; Ratnawulan, Ratnawulan (Jurnal Penelitian Pembelajaran Fisika, 2012)
KTSP in high school physics teaching requires learning device according to the characteristics of the material. In reality not yet available learning devices that require students to think scientifically and found the concept itself. On the other hand, teachers are expected to conduct classroom-based assessments, one of which is the assessment of the portfolio, a collection of works by students that is organized by interest, progress, achievement, and creativity of students in a specified period. How the development of learning physics using guided inquiry equipped models portfolio assessment in a circular motion of matter has not been developed. The research objective is to develop the learning of physics using guided inquiry equipped models portfolio assessment at the circular motion of matter are valid, practical and effective.This type of research is the development of research using model 4-D. Research procedures are define stage set and define the conditions of learning such as analysis of curriculum, learner analysis and concept analysis. Design phase is to prepare the device prototype stage of learning and development is done validity, and effectiveness of the learning practicality. The validity of the data collection instrument is a validation sheet RPP, modules, worksheets and portfolio assessment. Practicality data collection instruments are observation sheets and questionnaires practicality. Effectiveness of data collection instrument is the observation sheet and portfolio assessment.Validity of test results of the study obtained an average percentage value validation RPP was 84.6%, the module is 82% and LKS is 82.8%, this means that the category of learning is very valid, while the conclusion is valid assessment form without revision. Furthermore, the practicality of obtaining test results mean percentage of the value of practicality by a teacher questionnaire on RPP was 98%, the module is 96.5% and LKS was 96% and the percentage of the average value of the practicality of a questionnaire by the students on the module is 87.4% and LKS is 89.8% with the learning tools category that developed very practical. Furthermore, the effectiveness of the test result is the average value of the class students in the cognitive 66.7, affective domains is 61.2, psychomotor domains is 68 and the percentage of the average effectiveness base students activity is 86,3% . Conclusion of research is learning software developed very valid, very practical and effective.